DISSIPATION AT THE CORE-MANTLE BOUNDARY ON A SMALL-SCALE TOPOGRAPHY - Le Mouël J.L.; Greff-Lefftz M.; Narteau C.; Holschneider M. (My University, 2006)
The parameters of the nutations are now known with a good accuracy, and the theory accounts for most of their values. Dissipative friction at the core-mantle boundary (CMB) and at the inner core boundary is an important ingredient of the theory. Up to now, viscous coupling at a smooth interface and electromagnetic coupling have been considered. In some cases they appear hardly strong enough to account for the observations. We advocate here that the CMB has a small-scale roughness and estimate the dissipation resulting from the interaction of the fluid core motion with this topography. We conclude that it might be significant. Copyright 2006 by the American Geophysical Union.